Performing building vibration assessments by acoustic measurements. Issue 1 (March 2020) - Isavand, Javad; Peplow, Andrew; Kasaei, Afshar
This article presents an innovative application of the frequency domain decomposition method based on an acoustic and vibration response. Frequency domain decomposition method has been frequently used for operational modal analysis testing in the last decade to identify modal parameters for in-situ case studies. For these studies, the outputs of the vibration response through accelerometers have been employed in the analysis. In this article, the frequency domain decomposition method is employed, for the first time, to analyze both acoustic and vibration response of the building which is a novel application in building vibration response. As a case study, a cylindrical shaped seven-story building, which appears to be subjected to a vibration problem, was selected. In this research, both acoustic and vibration responses are captured to determine the source of this unknown excitation. The results show that using microphones, as an acoustic response, can be as reliable as accelerometers to identify forced vibration.